LGBT dalam Wacana Seksualitas Ditinjau dari Perspektif Seks dan Kekuasaan Foucault - Yuliana Yuliana (Prodi Sosiologi FISIP UPR, 2020)
Lesbian, Gay, Bisexual, Transgender hereinafter referred to as abbreviated as LGBT is an increasingly contemporary and unique phenomenon of society, this phenomenon is viewed from the perspective of sex and power Foucault, as a postmodern critique of dehumanizing modernity, where modern society is becoming more apathetic, consumptive, antisocial , and oppressive in its efforts to homogenize by rejecting diversity or plurality. Various basic values ??and ideas in postmo theory such as relativity and pluralism as well as the agreement to accept emotions and institutions is one that provides alternatives to address the LGBT phenomenon. The focus of this paper, trying to explain and describe the existence of LGBT associated with sexuality discourse in terms of the perspective of sex and power Foucault. Where, sexuality is used as an indicator to marginalize and narrow down the basic rights of Indonesian citizens, and this is the basis of the Indonesian LGBT community in demanding state legality over themselves so that they can live as socially, nationally and religiously as other citizens. Thus, it is expected to gain knowledge of new perspectives in seeing LGBT phenomena in Indonesia.